2007
DOI: 10.1128/jvi.02834-06
|View full text |Cite
|
Sign up to set email alerts
|

Direct Ex Vivo Analyses of HLA-DR1 Transgenic Mice Reveal an Exceptionally Broad Pattern of Immunodominance in the Primary HLA-DR1-Restricted CD4 T-Cell Response to Influenza Virus Hemagglutinin

Abstract: The recent threat of an avian influenza pandemic has generated significant interest in enhancing our understanding of the events that dictate protective immunity to influenza and in generating vaccines that can induce heterosubtypic immunity. Although antigen-specific CD4 T cells are known to play a key role in protective immunity to influenza through the provision of help to B cells and CD8 T cells, little is known about the specificity and diversity of CD4 T cells elicited after infection, particularly those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
110
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 62 publications
(113 citation statements)
references
References 110 publications
3
110
0
Order By: Relevance
“…In our previous studies on the primary response to infection with A/New Caledonia 20/99, we found that the HA-specific CD4 T cell repertoire was broad and included .30 epitopes (8). Comparison of HA sequences expressed by the pandemic H1N1 A/California/04/09 virus and other seasonal H1N1 strains of virus (not shown) indicates that there are segments of high sequence diversity where little T cell crossreactivity is expected and regions of complete conservation where we assume full cross-recognition.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous studies on the primary response to infection with A/New Caledonia 20/99, we found that the HA-specific CD4 T cell repertoire was broad and included .30 epitopes (8). Comparison of HA sequences expressed by the pandemic H1N1 A/California/04/09 virus and other seasonal H1N1 strains of virus (not shown) indicates that there are segments of high sequence diversity where little T cell crossreactivity is expected and regions of complete conservation where we assume full cross-recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza A/New Caledonia/20/99 and A/California/04/2009 E3 viruses were prepared as previously described (8) and used to infect APCs. APCs purified as described above were washed in serum-free DMEM media and infected with virus [multiplicity of infection (MOI) of 1 or 10 as indicated in the figure legends] for 1 h in serum-free media at 37˚C, followed by dilution and washing with complete culture media, described above.…”
Section: Infection Of Apcsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single cell suspension from the LN of an individual mouse was prepared and depleted of non-CD4 T cells as described previously (50). During kinetic experiments, LN from an individual mouse was enriched for CD4 T cells by negative selection (Miltenyi Biotech).…”
Section: Methodsmentioning
confidence: 99%
“…Influenza virus A/New Caledonia/20/99 was prepared in the allantoic cavities of embryonated chicken eggs, as described previously (46). Influenza virus A/California/04/2009 E3 (referred to below as A/California; generously provided by David Topham at the University of Rochester) is known to contain alterations in the HA gene resulting in three amino acid differences from the original strain isolated from humans (27).…”
Section: Influenza Virusmentioning
confidence: 99%